2014
DOI: 10.1002/aenm.201400107
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Carbon Decorated Li3V2(PO4)3 as a Bicontinuous Cathode with High‐Rate Capability and Broad Temperature Adaptability

Abstract: and fair theoretical specifi c capacity (197 mAh g −1 for complete extraction of three lithium ions when charged to 4.8 V, 133 mAh g −1 when cycled between the potential window of 3.0-4.3 V). [12][13][14] In particular, because of its sodium super ionic conductor (NASICON) structure, monoclinic Li 3 V 2 (PO 4 ) 3 provides a 3D pathway for Li + insertion/ extraction, which results in a very high ion diffusion coeffi cient (from 10 −9 to 10 −10 cm 2 s −1 ). [15][16][17][18][19] However, Li 3 V 2 (PO 4 ) 3 suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 47 publications
(96 reference statements)
2
48
0
Order By: Relevance
“…All the Nyquist plots were obtained at an amplitude of 10 mV versus the same potential of 0.8 V with a frequency Fig. 39 (b) Charge/discharge curves of the Bi@C core-shell NWs at a current density of 100 mA g −1 .…”
Section: Composition and Structural Characterizationmentioning
confidence: 99%
“…All the Nyquist plots were obtained at an amplitude of 10 mV versus the same potential of 0.8 V with a frequency Fig. 39 (b) Charge/discharge curves of the Bi@C core-shell NWs at a current density of 100 mA g −1 .…”
Section: Composition and Structural Characterizationmentioning
confidence: 99%
“…The theoretical capacity is 131 mAh/g, corresponding to the extraction of two Li + ions. However, m-LVP exhibits multiple plateaus in the discharge curves at 4.1, 3.7, and 3.6 V. [30][31][32] In comparison, r-LVP shows more appealing discharge curves with the very flat plateau at 3.75 V vs. Li + /Li, although it cannot be directly synthesized. Nazar et al first reported the synthesis of r-LVP through a topotactic ion-exchange from r-Na 3 V 2 (PO 4 ) 3 in the concentrated LiNO 3 solution.…”
Section: Introductionmentioning
confidence: 99%
“…Its high working potential (~4.0 V) can better satisfy the requirements of lithium ion batteries in electric vehicles (EVs) and hybrid electric vehicles (HEVs). Therefore, the Li 3 V 2 (PO 4 ) 3 cathode material has been developed to replace in lithium ion batteries [9,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%